Reading difficulties and factors affecting reading difficulties of students of grade 1 elementary school - Siti Rohimah (Mitra Palupi, 2021)
Background: Learning to read in elementary schools which is carried out at the first grade level is an early stage of reading learning or called beginning reading. Purpose: The purpose of this study was to determine the extent to which new students in elementary school (grade 1) were able to read and to know the difficulties faced by students when reading and its factors. Design and methods: The method used is a qualitative method using descriptive analysis. In this study, researchers went directly to the center of the field individually to obtain data from research subjects, while the subjects in this study were 1st grade elementary school students, 1st grade parents in several schools in East Bogor. The data collection technique used by the researcher is interviewing parents of grade 1 elementary school students and direct observation of students' abilities. Results: The reading ability of grade 1 elementary school students who have been observed in the reading test there are some students who are fluent in reading without help and without stuttering. There are two factors that affect reading difficulties, internal factors and external factors. Internal factors can be seen from the physical students. Physical weakness can affect reading difficulties. External factors of students that can affect reading difficulties are factors from the social environment and the most influential is the role of parents who accompany children to read at home. Parents who do not participate in the development of students' reading will hinder students' reading skills.